A Note on a Generalized Discounted Penalty Function in a Sparre Andersen Risk Model Perturbed by Diffusion. (3rd December 2013) - Liu, Chaolin; Zhang, Zhimin
Abstract : We consider a Sparre Andersen risk model perturbed by diffusion where the interclaim times are generalized Erlang( n ) distribution. Generalized discounted penalty functions incorporating the maximum surplus before ruin are studied. We derive the integrodifferential equations and give the solutions for the generalized discounted penalty functions.